Arthroscopic synovectomy and radiosynoviorthesis: a treatment option for recurrent arthritis symptoms in patients with pachydermoperiostosis - S. Warwas; C. Specker; M. Jäger; S. Landgraeber (PAGEPress Publications, 2013)
Pachydermoperiostosis as the primary form of hypertrophic osteoarthropathy is a rare hereditary disorder with a number of characteristic findings, e.g. periosteal hypertrophy, digital clubbing and pachydermia. Further typical symptoms include arthritic manifestations in all major joints. Literature review showed that therapeutical approaches usually focus on medical therapy alleviating chronic polyarthritis by controlling inflammation. In the case presented in this report anti-inflammatory therapy appeared to have been insufficient since knee arthritis persisted. Arthroscopic synovectomy and radiosynoviorthesis were performed consecutively. Postoperative and follow-up examinations indicate that this combined therapy reduces pain, increases range of motion and improves overall mobility, and is thus of lasting benefit to the patient.